MINUMAN FUNGSIONAL TERIPANG PASIR (Holothuria scabra) DAN TERIPANG HITAM (Holothuriaatra) - Nurul Afifah Elfath; R. Marwita Sari Putri; Azwin Apriandi (Marinade, 2020)
Aquatic resources such as sand teripang (Holothuria scabra) and black sea cucumber (H. atra) can be made into functional drinks. This research was conducted in 2 stages: 1) preparation of raw materials for Holothuria scabraand H. atra.2) formulation of functional beverage products. The objectives of this study are: 1) Knowing the results of proximate analysis on Holothuria scabraand H. atra. 2) Knowing the results of the analysis of bioactive saponins and antioxidants in functional drinks Holothuria scabraand H. atra. The results of this study concluded that the best functional formulations of Holothuria scabraand H. atradrink based on organoleptic1*)tests were functional drinkwith MFKT3 formulation with concentrations of Holothuria scabraand H. atra30%, 20% Rosella, 10% Ginger, 10% Lemongrass, 10 Kalamansi Orange %, Sugar 20%. The results of the analysis of Holothuria scabraand H. atrafunctional drinks in the nutritional component of water content were 89.17% and 89.16%, ash content 5.19% and 1.93%, protein content 5.06% and 7.74% , fat content 0.29% and 0.29%, carbohydrate content 0.27% and 0.87%. The antioxidant activity found in functional drinks of Holothuria scabraand H. atrais very weak, because the IC50 value is greater than 0.20 mg / ml or 200 ppm which is 1621 ppm. Saponins in functional drink extracts are identified by the formation of foam or foam.Aquatic resources such as sand teripang (Holothuria scabra) and black sea cucumber (H. atra) can be made into functional drinks. This research was conducted in 2 stages: 1) preparation of raw materials for Holothuria scabraand H. atra.2) formulation of functional beverage products. The objectives of this study are: 1) Knowing the results of proximate analysis on Holothuria scabraand H. atra. 2) Knowing the results of the analysis of bioactive saponins and antioxidants in functional drinks Holothuria scabraand H. atra. The results of this study concluded that the best functional formulations of Holothuria scabraand H. atradrink based on organoleptic1*)tests were functional drinkwith MFKT3 formulation with concentrations of Holothuria scabraand H. atra30%, 20% Rosella, 10% Ginger, 10% Lemongrass, 10 Kalamansi Orange %, Sugar 20%. The results of the analysis of Holothuria scabraand H. atrafunctional drinks in the nutritional component of water content were 89.17% and 89.16%, ash content 5.19% and 1.93%, protein content 5.06% and 7.74% , fat content 0.29% and 0.29%, carbohydrate content 0.27% and 0.87%. The antioxidant activity found in functional drinks of Holothuria scabraand H. atrais very weak, because the IC50 value is greater than 0.20 mg / ml or 200 ppm which is 1621 ppm. Saponins in functional drink extracts are identified by the formation of foam or foam.